Young children in day and night care: negotiating and constructing belonging during daily arrivals. Issue 12 (1st December 2016) - Salonen, Eija; Laakso, Marja-Leena; Sevón, Eija
ABSTRACT: The paper aims at understanding the processes related to young children's belonging during daily arrivals at day and night care. Two aspects of a child's belonging are considered: membership and sense of belonging. Data were gathered by ethnographic observation of 8 children aged from 20 to 36 months in two Finnish day care centres offering day and night care. Arrival episodes taking place at different times of day were analysed qualitatively based on the children's actions and expressions. During these episodes, the children negotiated and constructed their belonging by interacting with adults, peers and material objects. These interactions took place within varying social and material surroundings and according to different daily routines that sometimes challenged the child's belonging. The results underline the importance of sensitive responsiveness by educators to young children's initiatives in supporting children's belonging during daily arrivals at day and night care.